Feeling a deep sense of loneliness: Chinese late‐life immigrants in New Zealand. (5th July 2022) - Zhao, Ivy Yan; Holroyd, Eleanor; Wright‐St Clair, Valerie A.; Wang, Shan Shan; Garrett, Nick; Neville, Stephen
Abstract: Objectives: To explore Chinese late‐life immigrants' perceptions of loneliness and social isolation. Methods: A qualitative descriptive methodology underpinned this study. In‐depth individual interviews were conducted in Mandarin with purposively recruited participants. The twenty‐three participants in the study had all emigrated from China, were 65–80 years old on arrival and had lived in New Zealand for between 2.5 and 16 years. An inductive thematic analytic process was undertaken. The COREQ checklist was followed to ensure study rigour. Results: Three themes, 'high value placed on meeting family obligations', 'feeling a deep sense of imbalanced intergenerational reciprocity' and 'moving away from filial expectations', were identified. Confucianist values of 'women's domestic duty of caring for grandchildren', 'filial piety', and 'saving face' to be accepted and respected by others negatively attributed to participants' understandings and experiences of loneliness. To plan for increasing frailty and to avoid family conflict while ameliorating potential loneliness, some participants reluctantly discarded prior customary filial piety expectations in favour of formal aged care options. Conclusions: Participants' profound sense of loneliness was seen to be attributed to their deeply rooted cultural values and backgrounds from having lived for a significant period of time in China. Loneliness occurred as a result of the resettlement process in later life. These experiences highlight the importance of using cultural framing that takes into account beliefs and adaptations to host societies anticipated during the process of late‐life immigration.